Human Machine Interface for Automation System of Handling Station - Al Amin; Risfendra Risfendra (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2019)
Industries have implemented automation technology to increase their productivity. One machine that applies automation technology is the handling station. This machine is useful for moving parts or components in the industry. For the performance of this machine to be monitored directly, we need a system that can control and monitor the work process of this tool. This article is an explanation of the results of the study aimed at designing the HMI handling station automation system using a PLC as its controller, HMI as a media for operation and monitoring of machines, magnetic sensors, inductive sensors and pressure sensors to detect machine conditions. Research conducted using quantitative methods. After testing, the system can be monitored and controlled through HMI, besides that data recording carried out with a data logger can also record the system work process directly when the system is run.